Exploration of stacking effects of carbon/glass fabric in polymer hybrid composites: analysis of mechanical properties - Kaushlendra Kumar; Yadvendra Kumar Mishra; Jogendra Kumar; Vaibhav R. Pannase; Amol B. Dhumne; Vijay L. Bhambere; Gopal R. Bhad; Prasanjeet H. Bhagat; Rashtrapal B. Teltumade; Anirudh M. Shende (Discover Applied Sciences)
Abstract Hybrid composites, a cornerstone of modern engineering, have been the subject of a groundbreaking investigation. This research delves into the impact of changing the stacking configuration on the characteristics of glass and carbon configuration woven fabric-reinforced laminates. Fabricating different configurations of hybrid laminates using cost-effective hand layup techniques and their performance evaluation through uniaxial tensile test and flexural strength has yielded fascinating results. The tensile strength specimen was prepared as per ASTM D3039 and for flexural test ASTM D7264. The findings demonstrate that stacking laminate CGC has higher tensile strength (418.99 MPa) and flexural strength (342.99 MPa) than other stacking configurations of studied hybrid composites. Also, the fracture analysis evaluates using a high-resolution setup to comprehend the mechanism of failure interply hybrid composites. In addition, design and analytical analysis were done to analyze the tensile and flexural strength of different GC, GCG, and CGC stacking configurations. The finding demonstrates the feasibility of the CGC stacking configuration for load structural applications, marking a significant advancement in materials science and engineering.